Analisis Pengaruh Keterbukaan dan Audit Internal Terhadap Penerapan Good Corporate Governance Pada Perusahaan Daerah Air Minum (PDAM) Tirta Sakti Kerinci Tahun 2017 - Maryanto Maryanto (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2018)
Disclosure of information is an openness and honesty of information within a company that the government is responsible for its trusting resources in accordance with the laws and regulations in order to know openly the circumstances of a company based on the consideration that everyone has the right to know openly and thorough information. Disclosure of information and internal audit is an important factor in the implementation of good corporate governance. This study aims to determine the effect of information disclosure and internal audit on the implementation of good corporate governance in water utility company PDAM Tirta Sakti Kerinci Year 2017. Population and sample in this study are internal auditors who are in the Division of Internal Control Unit (SPI) working on PDAM Tirta Sakti Kerinci samples taken as many as 12 people. The sample in this research use purposive sampling technique. Based on the research that the authors do, show that There is a significant influence between the Public Information Disclosure Against the Application of Good Corporate Governance in Regional Water Company PDAM Tirta Sakti Key words: Information Disclosure. internal audit and Good Corporate Governance